STOMATAL DENSITY VARIATION IN BEECH AND HOLM OAK LEAVES COLLECTED OVER THE LAST 200 YEARS - Paoletti, E; GELLINI, R (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1993)
In leaf samples of Fagus sylvatica L. and Quercus ilex L. collected over the last 200 years a reduction has been observed in the stomatal density of 43% and 28% respectively. The ecological implications, particularly concerning atmospheric CO2 increase and drought tolerance, are discussed.
Keywords: ATMOSPHERIC CO2 INCREASE; FAGUS-SYLVATICA; QUERCUS-ILEX; stomatal density